Pengaruh Ukuran Perusahaan, Kualitas Kap, Tingkat Leverage Dan Komite Audit Terhadap Audit Delay(Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2015) - Pramita, Dina Adi, Drs. Wahyono, M.A., Akt., CA (2017)
The purpose of this research is to find out whether the size of company, quality of KAP, level of leverage and audit committee are the factors that affect audit delay in the manufacturing companies on the Indonesia Stock Exchange (IDX) period 2013-2015. Purposive sampling method is used to sample population. The number of samples taken was 111 companies of manufacturing industries which are listed in IDX period 2013-2015. Analysis of data using multiple linear regression analysis. The result of the research show that quality of KAP have influence to audit delay, while the size of company, level of leverage and audit committee do not have any influence towards audit delay.